MOTIVASI PEMBELAJARAN SISWA DALAM PEMBELAJARAN PENJASKESREK DI SEKOLAH SMK TIGAMA PEKANBARU MELALUI PEMBELAJARAN DARING - Alrifki, M. Agum; Sulastio, Agus; Syahriadi, Syahriadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Based on observations in the field that students lack motivation in learning due to lack of internet quota and others. The purpose of this research is to find out online learning according to the teacher's perspective and student motivation in knowing how effective online learning is in the Physical Education subject. This type of research is descriptive research. The population in this study were male students, totaling 558 people. The sampling technique was taken by Stratified Proportional Random Sampling, where the sample was taken by 10% of each strata or class, namely 10% of 558 male students so that a sample of 56 people was obtained. The technique of collecting data is by observing and distributing questionnaires to male students who have been selected as samples. Data analysis technique is to use descriptive statistics with frequency tabulation. The findings show that on intrinsic motivation, the statements answered by the respondents for the criteria of strongly agree (SS) are 19.75%, the criteria for agree (S) are 58.5%, the criteria for doubt (RG) are 14.2%, the criteria are not agree (TS) of 6.58%, and the criteria for strongly disagree (STS) of 1% with an achievement level of 77.14% are categorized as sufficient. As for extrinsic motivation, the statements answered by the respondents for the criteria of strongly agree (SS) are 17.25%, the criteria for agree (S) are 54.2%, the criteria for doubt (RG) are 16.1%, the criteria for disagree (TS) are 9.63% , and the criteria for strongly disagree (STS) of 2.72% with an achievement level of 74.64% are categorized as sufficient. So the conclusion is that the intrinsic and extrinsic motivation of students are in the sufficient category. To get the level of achievement categorized as very good, it is necessary to increase the motivation, both from within students (intrinsic) and from outside students (extrinsic).Key Words: Motivation, online learning